Help-seeking behavior of male college basketball players: Context, process, barriers, and intervention - Villasor, Ramon Eduardo Gustilo (Animo Repository, 2009)
This study explored the help-seeking behavior (HS) among male college basketball players, the context it takes place, the process involved, the specific barriers, and the possible interventions to promote help-seeking. This is a two-part study. A survey was initially conducted to establish the help-seeking preferences of the student-athletes. The second part of the study involved the preparation and try-out of a student-athlete intervention to promote help seeking behavior. A total of 114 student-athletes and 19 identified help-givers from 8 schools affiliated with the University Athletics Association of the Philippines (UAAP) and National Collegiate Athletic Association (NCAA) participated in the study. Among the measures used was the Barriers to Help Seeking Scale (BHSS). Content analysis, descriptive and inferential statistics were employed. Results showed that student-athletes were more likely to seek help for concerns that they could not handle independently. Typical concerns were time management, financial and academic difficulties as well as the lack of sufficient rest. Student-athletes sought help from help-givers at least five or more times over the course of six months. Parents, friend(s), and siblings were recognized as preferred helpers. Experience and approachability were seen as preferred help-givers qualities. The house of the preferred helper was seen as the most ideal help-seeking venue. The preferred help-seeking process is to identify a problem and select a help-giver who could assist the student-athlete regarding his concern. The barriers to seeking help were more internal than external. Findings have implications with regards to counseling.